Effective communication and group cohesiveness in the outdoor recreation program curriculum / Syaza Nur Nadirah Afzainizam, Ellail Ain Mohd Aznan and Ahmad Fikri Mohd Kassim - Afzainizam, Syaza Nur Nadirah; Mohd Aznan, Ellail Ain; Mohd Kassim, Ahmad Fikri (Universiti Teknologi MARA, Perlis, 2024)
This research endeavor seeks to explore the correlation between effective communication and group cohesiveness within the framework of outdoor recreational programs' curriculum. The study delves into the two fundamental components of effective communication: external perception encompassing clarity and information dissemination, and internal dissemination focusing on conflict resolution. In addition, the analysis of group cohesiveness entails an examination of four dimensions: individual attractions towards the group in social contexts (ATG-S), individual attractions towards the group in task-oriented settings (ATG-T), group integration-social (GI-S) and group integration-task (GI-T). A set of questionnaires based on Interpersonal Communication Skills (ICS) and Group Environment Questionnaire (GEQ) was completed by 100 students who took an outdoor recreation program. The respondent in this study consists of male (n=58) and female (n=42) respondents. The result revealed that external perception is positively associated with group integration social (GI-S) but negatively associated with individual attraction to the group task (ATG-T). Internal disseverance is not associated with individual attraction to the group social (ATG-S) and group integration task (GI-T). Conversely, negatively associated with group integration social (GI-S) and individual attraction to the group task (ATG-T). The findings underscore the complex interplay between external factors (such as perception) and internal group dynamics (such as conflict management) in shaping overall group cohesiveness and member engagement. These findings could help students and academicians understand the elements of group cohesiveness which can lead to more effective group work and improved learning experience for better educational achievement.